2020
DOI: 10.1177/0015732520920465
|View full text |Cite
|
Sign up to set email alerts
|

US Trade Actions Against China: A Supply Chain Perspective

Abstract: In 2018, the United States (US) Administration initiated several trade actions, including tariffs on China for unfair trade practices outlined by the US Trade Representative (USTR). In response, China filed requests for consultations with the World Trade Organization (WTO) and has implemented or threatened to implement increased tariffs on US products. In this article, the implications of current and potential US trade actions and responses by China on the US and global economy are estimated. We emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…These models have been applied successfully to examine economic impacts of health threats, such as influenza pandemics (see, e.g., Dixon et al 2010 , 2020 ; Prager et al 2017 ; Walmsley et al 2020 ). In particular, we use the ImpactECON Supply-Chain Model (Walmsley and Minor 2016 , 2020a ). This Model is adapted from one of the most widely-used CGE models, GTAP (Hertel and Tsigas 1997 ; Corong et al 2017 ), and has the extended capability for examining supply-chain impacts linked to economic activity and policies in the rest of the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These models have been applied successfully to examine economic impacts of health threats, such as influenza pandemics (see, e.g., Dixon et al 2010 , 2020 ; Prager et al 2017 ; Walmsley et al 2020 ). In particular, we use the ImpactECON Supply-Chain Model (Walmsley and Minor 2016 , 2020a ). This Model is adapted from one of the most widely-used CGE models, GTAP (Hertel and Tsigas 1997 ; Corong et al 2017 ), and has the extended capability for examining supply-chain impacts linked to economic activity and policies in the rest of the world.…”
Section: Introductionmentioning
confidence: 99%
“… 1 See also Walmsley and Minor ( 2020a , b ) for a detailed explanation of model and data used in this analysis. …”
mentioning
confidence: 99%
“…Walmsley and Minor () produce a version of GTAP that they refer to as a supply chain model. The standard version of GTAP identifies flows of commodity c from source country s to destination country d but then assumes that the source composition of imported c in d is the same for all users.…”
Section: Cge Modelling: the State Of Play And What Has To Be Done To mentioning
confidence: 99%
“…Several researchers utilized computable general equilibrium (CGE) models to address this subject. Walmsley and Minor () examined what might happen if NAFTA ended and found that trade, investment, and real gross domestic product (GDP) would decline in each member country. Robinson, Gornostay, de Bolle, Joseph, and Korb () explored the possible employment effects of a U.S. withdrawal from NAFTA and concluded that about 187,000 export‐related U.S. jobs would be lost, with agriculture being one of the most adversely affected sectors.…”
Section: Introductionmentioning
confidence: 99%